2018
DOI: 10.1021/acs.jpclett.8b01396
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Single-Point Mutations on the Excitonic Structure and Dynamics in a Fenna–Matthews–Olson Complex

Abstract: Hole burning (HB) spectroscopy and modeling studies reveal significant changes in the excitonic structure and dynamics in several mutants of the FMO trimer from the Chlorobaculum tepidum. The excited-state decay times ( T) of the high-energy excitons are significantly modified when mutation occurs near bacteriochlorophyll (BChl) 1 (V152N mutant) or BChl 6 (W184F). Longer (averaged) T times of highest-energy excitons in V152N and W184F mutants suggest that site energies of BChls 1 and 6, believed to play an imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 41 publications
3
12
0
Order By: Relevance
“…In summary, our results show that the excitonic structure and dynamics of the FMO complex are very sensitive to the local environment around BChl 6. Even a small change, such as a single-point mutation near BChl 6, can cause changes in several exciton states, resulting in a noticeable change in the absorption 31 and Khmelnitskiy et al 33 showed that most of the mutant spectra exhibited some degree of changes, but only the W184F mutant (near BChl 6) resulted in amplitude reversion of the 806 nm and 815 nm bands, which is consistent with our results. This is due to the position and orientation of BChl 6 in the FMO complex that enables strong couplings with its nearby BChls 5 and 7.…”
Section: ■ Results and Discussionsupporting
confidence: 93%
“…In summary, our results show that the excitonic structure and dynamics of the FMO complex are very sensitive to the local environment around BChl 6. Even a small change, such as a single-point mutation near BChl 6, can cause changes in several exciton states, resulting in a noticeable change in the absorption 31 and Khmelnitskiy et al 33 showed that most of the mutant spectra exhibited some degree of changes, but only the W184F mutant (near BChl 6) resulted in amplitude reversion of the 806 nm and 815 nm bands, which is consistent with our results. This is due to the position and orientation of BChl 6 in the FMO complex that enables strong couplings with its nearby BChls 5 and 7.…”
Section: ■ Results and Discussionsupporting
confidence: 93%
“…Populations determined by generalized Förster rates calculated according to §3. Adapted from [66]. (Online version in colour.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the trimeric organization with the same SDF for each BChl 3 leads to a triple splitting of the 825 nm absorption band. Adapted from[66]. (Online version in colour.)…”
mentioning
confidence: 99%
“…The Fenna–Matthews–Olson (FMO) pigment–protein complex, found in green sulfur bacteria, is one of the most thoroughly studied photosynthetic proteins (see Figure ). The primary function of FMO is to transfer the excitation energy from a much larger chlorosome antenna to the intramembrane reaction center complex, where electronic excitation initiates charge transfer process.…”
mentioning
confidence: 99%